Tone-Independent Orthogonalizing Lattice Equalization for Insufficient Cyclic-Prefix OFDM Transmissions. (21st December 2013) - Kim, Dong Kyoo; Lee, Yang Sun
Tone-independent orthogonalizing lattice per tone equalizer (TOL-PTEQ) is introduced and its convergence is analyzed. Cyclic-prefix redundancy, one of the major drawbacks of orthogonal frequency division multiplexing (OFDM), can be reduced by TOL-PTEQ. Fast convergence and low computational complexity of TOL-PTEQ are also suitable properties for packet-based wireless communications and detections in which OFDM is widely deployed for their modulation technique.